Професор Ф.М. Левон. Життєвий і творчий шлях (до 75-річчя від дня народження) - Kuznetsov, S.I.; Gorelov, A.M. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2013)
The milestones of a course of life and scientific activity of the scientist-forester, the ecologist, the known specialist in the field of an amenity planting and an afforestation, professor F.M. Levon are elucidated.